1991
DOI: 10.1099/00207713-41-3-417
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium tropici, a Novel Species Nodulating Phaseolus vulgaris L. Beans and Leucaena sp. Trees

Abstract: A new Rhizobium species that nodulates PhaseoZus vulgaris L. and Leucaena spp. is proposed on the basis of the results of multilocus enzyme electrophoresis, DNA-DNA hybridization, an analysis of ribosomal DNA organization, a sequence analysis of 16s rDNA, and an analysis of phenotypic characteristics. This taxon, Rhizobium tropici sp. nov., was previously named Rhizobium Zeguminosarum biovar phaseoli (type I1 strains) and was recognized by its host range (which includes Leucaena spp.) and nifgene organization.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
348
2
23

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 585 publications
(390 citation statements)
references
References 68 publications
17
348
2
23
Order By: Relevance
“…In recent years, progress towards the development of a more complete Rhizobium taxonomy has been made, and new species have been described: R. tropici (16), R. huakuii (3), and Rhizobium etli (25). Genomic relatedness between members of the family Rhizobiaceae has been revealed by modern approaches and has allowed the construction of phylogenetic trees and the proposal of possible modes of rhizobial evolution (7,14,31,33,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, progress towards the development of a more complete Rhizobium taxonomy has been made, and new species have been described: R. tropici (16), R. huakuii (3), and Rhizobium etli (25). Genomic relatedness between members of the family Rhizobiaceae has been revealed by modern approaches and has allowed the construction of phylogenetic trees and the proposal of possible modes of rhizobial evolution (7,14,31,33,35).…”
Section: Discussionmentioning
confidence: 99%
“…The main properties of a bacterial isolate can be described by its taxonomical position in relation to other strains. There are several Rhizobium species recognized at this time (10, 1.3, 24), and knowledge of rhizobial evolution and phylogeny obtained in recent studies allows the proposal of new rhizobial taxa (3,16,25). However, the current systematic description of the genus Rhizobium does not include many of the root nodule isolates from legumes of tropical (22, 37), arctic (21), and temperate (5, 12, 17) regions.…”
mentioning
confidence: 99%
“…Esse meio de cultura é utilizado para discriminar espécies de rizóbio (WANG et al, 1998;MARTINEZ-ROMERO et al, 1991). Como a composição original do meio LB apresenta 10 g L -1 de NaCl, para este estudo, além dessa concentração, foram também testadas as seguintes concentrações: 1, 2; 2,5; 3; 20; 30 e 50 g L -1 .…”
Section: Experimento 2: Tolerância De Rizóbio à Salinidade Em Meio Deunclassified
“…Nesse meio, a fonte principal de carbono é a peptona de caseína, que representa um fator limitante para o crescimento de algumas espécies bacterianas, pois, nem todas têm capacidade de degradá-la em meio de cultura. Essa característica tem sido usada como diferencial para a descrição de novas espécies bacterianas, inclusive rizóbio (WANG et al, 1998;MARTINEZ-ROMERO et al, 1991).…”
Section: Experimento 2: Tolerância De Rizóbio à Salinidade Em Meio Deunclassified
“…It is very well know that symbiotic relationship between shrub legumes and rhizobia is rather promiscuous and frequently unspecifi c (FRIONI et al, 1998;PUEPPKE;BROUGHTON, 1999;THRALL et al, 2001). On the other hand, in cross nodulation in greenhouse experiments, among different species and rhizobia strains (Center for Genomic Sciences, UNAM collection), a positive nodulation of A. farnesiana inoculated with Rhizobium etli (CFN42 T ), a Phaseolus vulgaris nodulant (very abundant in Mesoamerican soils) (SEGOVIA et al, 1993) was found (MARTÍNEZ-ROMERO et al, 1991). At the same time, S. americanum is able to nodulate under laboratory conditions, the very same hosts as R. etli and R. tropici and it also nodulates other Acacia species (TOLEDO, 2003).…”
Section: Biomass Productionmentioning
confidence: 99%